Vertical movement of the potassium ion in Quartzipsamment Entisols under sugarcane crop - Ucker, Fernando Ernesto; De-Campos, Alfredo Borges; Hernani, Luís Carlos; Macedo, Jose Ronaldo de; Melo, Adoildo da Silva (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to determine the vertical movement of the potassium ion in the profile of Quartzipsamment Entisols cultivated with sugarcane. Two experiments were conducted in field conditions. The first one consisted of an assessment of ion movement in the soil profile, down to 1.80-m depth, for two years, in an area cultivated with sugarcane and in another one under cerrado. The second one consisted of the evaluation of ion movement to a depth of 1.00 m, under two water regimes: natural and controlled. In the experiment under controlled conditions, evaluations were done with 0.5-m2 plots, delimited by galvanized sheets, receiving 80 kg ha-1 K2O followed by the addition of 1,200 mm of water. The area cropped with sugarcane showed greater soil organic matter content, greater pH, and, consequently, greater retention capacity of K+ in the superficial layers of the soil profile than the cerrado area. Moreover, in the area with sugarcane crop, the evaluation of K+ availability in the profile of the Quartzipsamment Entisol profile was affected by the adopted water regime (natural or controlled rainfall). Regardless of soil use, K+ moves rapidly through the soil profile.